α-Mangosteen as An Oxidative Inhibitor in Hepatocellular Carcinoma - Harliansyah Harliansyah; Nunung Ainur Rahmah; Kuslestari Kuslestari (Indonesian Society for Cancer Chemoprevention, 2021)
Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver and the second leading cause of cancer mortality worldwide. Many strategies to discover molecular-based therapy are currently being implemented to overcome the resistance in HCC treatment. Cancer research is more targeted at molecular level of natural ingredients treatment as chemoprevention to reduce carcinogenesis risk. One of the natural compounds that serve as chemopreventive agent is mangosteen. α-Mangosteen, a xanthone commonly found in the fruit hull of Garcinia mangostana Linn, possess as an antioxidant. This study aims to determine the levels of reactive oxygen species (ROS), malondialdehyde (MDA), and protein carbonyl (PC) as the biomarkers of oxidative stress on untreated HepG2 cells compared to α-mangosteen-treated HepG2 cells. The results indicated that α-mangosteen has a cytotoxic effect on HepG2 cells with IC50=242.58 μg/mL and reduced ROS level 23.15±4.29% at 200 μg/mL. The MDA level of HepG2 cells was not significantly higher than on WRL-68 by 7.6%, 17.93%, 28.8%, 35.32%, and 61.95% at 100, 200, 500, 800, and 1000 μg/mL respectively. α-Mangosteen at 100 and 200 μg/mL reduced protein carbonyl by 76.24 and 79.84% in HepG2 cells line while compared to normal liver cells line (WRL-68) significantly (P<0.05). In conclusion, α-mangosteen reduced levels of ROS, MDA and PC. Therefore, α-mangosteen is a potential anti-cancer agent through oxidative stress inhibition.Keyword: free radical, HepG2 cells, α-mangosteen, oxidative stress.